Ovaries of estrogen receptor 1-deficient mice show iron overload and signs of aging - Schröder, Sarah K.; Krizanac, Marinela; Kim, Philipp; Kessel, Jan C.; Weiskirchen, Ralf (Frontiers in Endocrinology, 2024)
Introduction Estrogens are crucial regulators of ovarian function, mediating their signaling through binding to estrogen receptors. The disruption of the estrogen receptor 1 (Esr1) provokes infertility associated with a hemorrhagic, cystic phenotype similar to that seen in diseased or aged ovaries. Our previous study indicated the possibility of altered iron metabolism in Esr1-deficient ovaries showing massive expression of lipocalin 2, a regulator of iron homeostasis. Methods Therefore, we examined the consequences of depleting Esr1 in mouse ovaries, focusing on iron metabolism. For that reason, we compared ovaries of adult Esr1-deficient animals and age-matched wild type littermates. Results and discussion We found increased iron accumulation in Esr1-deficient animals by using laser ablation inductively coupled plasma mass spectrometry. Western blot analysis and RT-qPCR confirmed that iron overload alters iron transport, storage and regulation. In addition, trivalent iron deposits in form of hemosiderin were detected in Esr1-deficient ovarian stroma. The depletion of Esr1 was further associated with an aberrant immune cell landscape characterized by the appearance of macrophage-derived multinucleated giant cells (MNGCs) and increased quantities of macrophages, particularly M2-like macrophages. Similar to reproductively aged animals, MNGCs in Esr1-deficient ovaries were characterized by iron accumulation and strong autofluorescence. Finally, deletion of Esr1 led to a significant increase in ovarian mast cells, involved in iron-mediated foam cell formation. Given that these findings are characteristics of ovarian aging, our data suggest that Esr1 deficiency triggers mechanisms similar to those associated with aging.